Overhearing Dialogues and Monologues: How Does Entrainment Lead to More Comprehensible Referring Expressions?. Issue 7 (3rd October 2018) - Tolins, Jackson; Zeamer, Charlotte; Fox Tree, Jean E.
ABSTRACT: People overhearing referential communication understand more when they listen in on dialogues rather than monologues. Some have proposed this is because entrainment selects better referential expressions. In a corpus analysis, we considered the role of addressees in contributing to entrainment and measured the degree to which particular perspectives were used across different speakers in dialogues and monologues. In a test of overhearer comprehension, we found that although descriptions from dialogues were more easily understood, the frequency by which perspectives were used also influenced comprehension across both dialogues and monologues. We conclude that entrained perspectives are not objectively better and cannot be used as the basis for explaining the benefit of listening to dialogues.